Identification and characterization of related substances in EVT-401 by hyphenated LC-MS techniques - Binan Zhu; Yuting Lu; Leilin Chen; Binbin Yu; Yuexin Liu; Min Song; Taijun Hang (Elsevier, 2017)
A sensitive and selective method was developed for the separation and characterization of related substances (RSs) in EVT-401 by hyphenated LC-MS techniques. Complete separation of the RSs was achieved with an Inertsil ODS-SP column (250 mm×4.6 mm, 5 µm) by linear gradient elution using a mobile phase consisting of 0.2% formic acid solution, methanol and acetonitrile. EVT-401 was found to be susceptible to acid, alkaline and oxidative stresses, while relatively stable under photolytic and thermal dry stress conditions. Fourteen RSs including six process-related substances and eight degradation products were detected and identified in EVT-401 with positive ESI high-resolution TOF-MS analysis of their parent ions and the corresponding product mass spectra elucidation, and some of them were further verified by chemical synthesis and NMR spectroscopy. The specific LC-MS method developed for separation, identification and characterization of RSs is valuable for EVT-401 manufacturing process optimization and quality control.